2021
DOI: 10.1037/emo0000744
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a temporal distancing emotion regulation task in adolescence.

Abstract: Adopting a temporally distant perspective on stressors, also known as using a temporal distancing emotion regulation strategy, can alleviate distress. Young adults' ability to adopt a temporal distancing strategy has previously been measured using an experimental temporal distancing task (Ahmed, Somerville, & Sebastian, 2018). In the current study, we evaluate the psychometric properties of this task in younger (N ϭ 345, aged 10-11) and older (N ϭ 99, aged 18-21) adolescents and explore developmental differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…We also hypothesised that this relationship between early language and regulation success would be mediated by the effect of language on distance projected into the future. Year 1 language was not related to distance projected into the future while engaging in temporal distancing, nor was distance projected related to regulation success (as reported previously; Suksasilp et al, 2020).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…We also hypothesised that this relationship between early language and regulation success would be mediated by the effect of language on distance projected into the future. Year 1 language was not related to distance projected into the future while engaging in temporal distancing, nor was distance projected related to regulation success (as reported previously; Suksasilp et al, 2020).…”
Section: Discussionsupporting
confidence: 65%
“…We previously reported a replication of the Ahmed, Somerville, & Sebastian (2018) findings in a population sample of younger adolecents (aged 10-11 years) and a community sample of older adolescents (age 18-21 years; Suksasilp, Griffiths, Sebastian, & Norbury, 2020). As in the original study, we found a reduction in negative mood when participants imagined the effect of a negative event in the future, compared to when they had imagined it's effect now, and we further demonstrated that this effect had adequate test-retest reliability.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…and arousal: 'How anxious/ stressed do you feel right now? '), in order to reduce the length and complexity of the task [21].…”
Section: Temporal Distancing Taskmentioning
confidence: 99%